REALISING GOOD GROWTH a practical guide for business leaders. (ROUTLEDGE, 2026)
Realising Good Growth is a practical and purposeful guidebook for leaders wishing to take a different path on a journey towards collective purpose and a better world, where profit is not the destination, just one of the sturdy pillars that supports the journey.Values to shape your journeyOur blueprint is drawn with values of sustainability, long-term vision, mutual enhancement and cooperation.Digital supportThe guidebook is supported by a range of integrated, tried-and-tested digital tools and accompanying website for practical use.What's in it for you and others?For businesses, the regenerative opportunity is about greater competitive advantage, retaining and attracting the best employees, enhanced innovation and productivity, and a greater return on all assets......But that fades into the shade in comparison to enhancing lives and enabling humanity to flourish.True success is measured not by profits alone, but by the lives we enrich and the future we create for all.Humanity has a big problem. Growth! More precisely the nature of growth and its consequences.We are passengers on a runaway train, hurtling toward a fractured and barren landscape. If we do not pull the emergency brake soon, we will leave our children stranded in a desolate wasteland, where the fertile fields of today are but a distant memory.But imagine a different outcome if this is resolved.Imagine a different path to follow, one less travelled, where businesses are a force for good.Imagine a regenerative economy led by businesses of all sizes pursuing an agenda of Good Growth - where employees have a deep sense of engagement and ownership in helping to grow businesses that deliver social value.Now, it is about experience, fulfilment and community - not one of self-centred endless consumption.